Research on the quality of milk and vegetable mince based on the concentrate of buttermilk - Юдіна, Тетяна Іллівна; Назаренко, Ірина Анатоліївна; Никифоров, Радіон Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents a complex of data characterizing the quality of the designed milk and vegetable mince. We have identified the shares of the main nutrients in the milk and vegetable mince and found out that the designed mince contains more nutrients than it is required by the standard. Thus, the share of dry matter in the new mince exceeds the standard share by 2.05-6.32 %, fat––by 0.80-0.82 %, carbohydrates, in particular mono- and disaccharides,––by 6.24-6.28 %, pectin––by 0.37-1.63 %, and cellulose––by 0.18-0.53 %, which proves feasibility of combining dairy and plant material. Calculation of the amino acid score for the milk and vegetable mince shows that the mince proteins are free from limiting amino acids, whereas the share of all essential amino acids exceeds the FAO/WHO standards, which proves high biological value of the mince. The research has proved that the relative biological value (RBV) and the rate of digestion by the main proteolytic enzymes make the designed mince excel the standard. The analysis of the obtained data additionally confirms the physiological phenomenon discovered by О. О. Pokrovsky. We have proved that vegetable raw materials used as mince ingredients enrich the designed produce with vitamins and minerals. The research shows that the shares of vitamins in the milk and vegetable mince increase (vitamins of group B––10.35-12.06 times, vitamin А––4.50-5.50 times, and vitamin С––5.60-7.02 times) in comparison with the standard while the content of all mineral elements makes the designed mince excel the standard. Therefore, the designed mince is a promising raw material for manufacturing culinary products, which allows expanding the range of products with a higher nutritional and biological value.